UPAYA PENINGKATAN PENGETAHUAN IBU HAMIL DAN SUAMI DI PUSKESMAS PUTRI AYU KOTA JAMBI - Ratu Kusuma (Jurnal Abdimas Kesehatan (JAK), 2019)
Lack of knowledge of pregnant women and husband about pregnancy and various things related to pregnancy have a negative influence on the health of the pregnant women, fetus /child, family and community. One effort that can be done by nurses is to provide health education to pregnant women and husband. Puskesmas Putri Ayu is  a community health center as partner that has carried out sintegrated antenatal services according to the program, but in its implementation a little pregnant women were accompanied by their husbands when conducting antenatal visit. The target and outcome of community service activities is to increase the knowledge of pregnant women and husband about pregnancy, various needs during pregnancy, various changes that occur during pregnancy and the importance of husband's support for pregnant women. The implementation method used is survey, observation, interview, discussion, and demonstration through health counseling and pregnancy exercises  in the prenatal  class. This activity was conducted in 3 sessions, followed by 32 pregnant women and 6 husbands. The result of this activity is that most pregnant women who attend antenatal visit are accompanied by sister/parent/aunt, a little  pregnant women accompanied by their husbands. The husband's absence is caused by work factor and the assumption that it is better to be accompanied by another parent or sister, and the husband feels ashamed to gather with other pregnant women in the prenatal class. A little husbands were willing to take part in the prenatal  class, most of them waited outside after being given counseling, several pregnant women and husband began to understand and actively ask question and express their problems.